Before Grievances turn into Ethno-political Violence: The Case of Gilgit-Baltistan politics - Abrar Hussain; Nasir Ali; Muhammad Zuha (Journal of Peace, Development and Communication, 2023)
Gilgit-Baltistan (GB) is de-facto constitutional and de-jure administrative part of Pakistan. Since annexation of the region with Pakistan in 1947 several reforms have gradually been introduced to uplift the region at par with other provinces of the country, however, still there remain inequalities in terms of socio-economic indicators in addition to constitutional and identity lacuna. Political processes emanate from indigenous (local) and mainstream (Pakistan) political parties. Both simultaneously shape emerging political dynamics that cast deep imprints in minds through political socialization in people of GB. To ensurestable integration of the region into constitution and federation of Pakistan requires concrete political empowermentof the regionstrengthening democratic culture and inclusive institutions in the region.